Semantic challenges caused by abbreviations of Arabic economic and business terms for undergraduates in China - Shuhan, Ma; Abdul Jabar, Mohd Azidan; Fang, Ng Chwee (Human Resource Management Academic Research Society, 2022)
The economic usefulness of abbreviations has become essential as language tools in human society, especially for international economic and business activities. This study has explored the semantic challenges of abbreviations of Arabic economic and business terms for third-grade undergraduates majoring in Arabic language without basic backgrounds in the economy and business in China. The present study adopted a quantitative study design to test 30 students’ abilities in understanding abbreviations. The data analysis used simple mathematical statistics to calculate results and comprehensive analysis within terminological frameworks with interdisciplinary semantic theories to mainly analyze correct answers and students’ answers. Thus, we have found that three-quarters of students faced varying degrees of semantic challenges in the abbreviations of Arabic economic and business terms. In this regard, the current study will improve students’ understanding of abbreviations, and remind instructors in the courses of Arabic for business purposes to explain such knowledge.